Penerapan Model Antrian Untuk Mengoptimalisasikan Pelayanan Pada Loket Pengambilan Obat Di Puskesmas Desa Meko - Molanu, Irmawati; Jaya, Agus Indra; Nacong, Nasria (Universitas Nusa Cendana, 2024)
Queuing is a waiting line state where a number of entrants are involved to get services from a service providing facility. One example of queuing activities that are common in the community is taking medicine at the Meko Village Health Center. The purpose of this study was to obtain an optimal queuing model at the drug collection counter at the Meko Village Health Center. Based on the analysis, at this time the service at the drug collection counter at the Meko Village health center that uses queues with a single channel single phase (M/M/1) model is not optimal. To optimize services, the application of the multi-channel single phase multiple line queue model (M/M/c) where c = 3 results in a measure of system performance, namely the probability of no customers in the system ( ) is 0.034 = 3.4%, the service utility rate (ρ) is 0.866 = 86.6%, number patient in the queue ( ) is 5 customers, number patient in the system ( ) is 8 customers, waiting time in the queue ( ) is 22,38 minutes, and waiting time in the system ( ) is 34,38 minutes. By applying the multi-channel single phase (M/M/c) multiple line queue model, it becomes an alternative solution in providing good and optimal service to patients at the Meko Village health center.